2010
DOI: 10.1002/bio.1253
|View full text |Cite
|
Sign up to set email alerts
|

Spectrofluorimetric determination of aluminium using 2‐hydroxy‐1‐naphthylidene‐(8‐aminoquinoline)

Abstract: A sensitive and selective spectrofluorimetric method has been developed for the rapid determination of aluminium. This method is based on the complex formation between aluminium and 2-hydroxy-1-naphthylidene-(8-aminoquinoline) (HNAQ). The optimum conditions for the complex formation were a metal-to-ligand (M : L) stoichiometric ratio of 1:1, a pH of 5.5 and a 0.20 m acetate buffer. The fluorescence of the complex was monitored at an emission wavelength of 502 nm with excitation at 438 nm. Under these condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…It was found that Al(III) in saliva reached a maximum of 101.2 ng mL −1 at 3.0 h. The absorption rate constant k a , elimination rate constant k and half‐life t 1/2 of Al(III) were 1.378 h −1 , 0.264 h −1 and 2.624 h, respectively. Compared with other reported methods, summarized in Table , including FL , inductively coupled plasma atomic emission spectroscopy , AAS and CL , it was shown that the proposed CL method improved the LOD by three orders of magnitude, and Al(III) could be determined at the pictogram level in biofluid with remarkable sensitivity.…”
Section: Introductionmentioning
confidence: 88%
“…It was found that Al(III) in saliva reached a maximum of 101.2 ng mL −1 at 3.0 h. The absorption rate constant k a , elimination rate constant k and half‐life t 1/2 of Al(III) were 1.378 h −1 , 0.264 h −1 and 2.624 h, respectively. Compared with other reported methods, summarized in Table , including FL , inductively coupled plasma atomic emission spectroscopy , AAS and CL , it was shown that the proposed CL method improved the LOD by three orders of magnitude, and Al(III) could be determined at the pictogram level in biofluid with remarkable sensitivity.…”
Section: Introductionmentioning
confidence: 88%
“…The luminescence data, listed in table 10 (without solvent correction), are assigned as intra-ligand 1 (π-π*) fluorescence [46]. The relative quantum yields of ligands HL 1 and HL 2 and all three complexes are determined using coumarin 6 in methanol as the reference (Φ f = 0.78) at λ ex = 430 nm [47]. The quantum yields for HL 1 and HL 2 are 0.05 and 0.08, respectively.…”
Section: Geometry Optimizationmentioning
confidence: 99%
“…Many fluorogenic reagents have been used for the determination of aluminium based on the formation of metal complexes. These include quercetin [14], morin [15,16], purpurin [17], lumogallion [18,19], 8-hydroxyquinoline-5-sulfonic acid [20], oxine [21,22], chromotropic acid [23,24], salicylaldehyde picolinohydrazone [25], N,N-disalicylidene-1,3diamino-2-hydroxy propane [26], 8-hydroxy-7-(4-sulfo-1-naphthylazo)-5-quinoline sulfonic acid (HSNQ) [27], N-o-vanillidine-2-amino-p-cresol [28]) and 2-hydroxy-1-naphthylidene-(8-aminoquinoline) [29].…”
Section: Introductionmentioning
confidence: 99%
“…As part of our recent method development [15,16,27,29,30] for the sensitive monitoring of aluminium ions in water, we report herein a novel method for the determination of aluminium using the fluorogenic ligand N-((2-hydroxynaphthalen-1-yl) methylene) acetylhydrazide (HNMA). Factors affecting complexation and the effects of foreign species were studied.…”
Section: Introductionmentioning
confidence: 99%